THE ROLE OF EXTERNAL VOLUME EXPANTION AND CELL ASSISTED LIPOGRAFTING IN IMPROVING POST BURN SCAR QUALITY, A RANDOMIZED CLINICAL STUDY - Hesham Abdelmoniem Eissa, Khaled Mohammed Hassan, Ahmed Adel Nor El Den, Ahmed Mahrous Mohamed (Chelonian Research Foundation, 2024)
Throughout history, scars have represented a problem, where most of the solutions are unsatisfactory. The search for a more successful method with long‑term, better results for different skin types remains the main challenge facing plastic surgeons. External volume expansion (EVE) devices mechanically stretch and stimulate tissues by suction in a non‑invasive manner. Stretch releases the skin and it has been postulated by different studies that the mechanism of action could be direct mechanical action on individual cells, induction of ischemia, inflammation and soluble mediators which stimulates cell proliferation, adipogenesis and, most importantly, vascular remodeling.. Platelet-rich plasma (PRP) is an autologous blood-derived product enriched in platelets, growth factors and chemo/cytokines delivered in a concentrated volume of plasma. PRP has the potential to deliver a high concentration of growth factors to target tissues by virtue of the contents within the alpha and dense granules. A relatively new option for the treatment of scar tissue is the use of autologous fat grafting, first described by Neuber in 1893 and later refined by Coleman. Autologous fat grafting has a volume‑increasing effect and is thought to stimulate the neosynthesis of collagen fibers, which therefore increases dermal thickness, resulting in an improvement in skin quality. The use of autologous fat grafting has increased in common practice, but to date there is a lack of scientific evidence regarding the effects on scar tissue. Fat grafting for soft tissue defects and volume expansion presents an appealing alternative or adjunct to reconstruction with flaps or implants because of its simplicity of technique and low morbidity associated with it. However, the unpredictable survival (30%–80%) and the inverse correlation of survival to injection volume have led to skepticism about its utility.